Various Applications of IoT-based Weather Monitoring Systems in the Agricultural Sector for Bangladeshi Farmers. - MD SOFIQUL ISLAM; Md.Saiful Islam; Jahangir Hossain Rabbi; A S M Binjer Anayet Biddut; Md.Salman Hossen (ReCIBE)
Climate change is playing a significant role in agriculture. As an agriculturally efficient country like Bangladesh, smart farming is needed to effectively help farmers adapt to this climate change. The main objective of this IOT based project is to increase efficiency, especially in mushroom farming and shrimp fishing. In both cases, smart farming requires real-time weather information from farmers. This system enables farmers to monitor temperature, humidity, water level at any moment from anywhere in the world using their smartphones. This system focuses on local farmers in different districts of Bangladesh, where they are able to monitor the weather for their decision-making and optimize the concept of real-time scheduling for specific food crops. Local rice farmers who are using real-time weather monitoring systems can know the exact moment of their rains, which helps them determine the time to harvest their mature rice. This approach will open up a new avenue for our local farmers through which they can increase their capacity through mushroom cultivation and shrimp farming more than before, which will help boost the economy of a country like Bangladesh a lot.